How much of John Maynard Keynes can we find in Franco Modigliani? - Pasinetti, Luigi L. (PSL Quarterly Review, 2012)
Franco Modigliani's first published paper became one of the basic documents of modern Keynesian economics. In it he formalized the model (or at least one model) implicit in The General Theory. Modigliani argued that the characteristic Keynesian conclusions rest fundamentally on the (realistic) rigidity of nominal wages. In particular, he showed that if wages and prices were flexible, the liquidity preference theory of money could not generate persistent involuntary unemployment; but if wages were rigid, even the quantity theory of money could do so. Sixty years later Modigliani returned to a statement of "the Keynesian gospel" and proposed essentially the same interpretation. This paper reviews and discusses this approach to macroeconomics, with some reference to its implications for policy. JEL Codes: B22, B31